2017
DOI: 10.1159/000481657
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/mTOR Inhibitors in the Treatment of Luminal Breast Cancer. Why, When and to Whom

Abstract: Estrogen receptor (ER) signaling represents the main driver of tumor growth and survival in luminal breast cancer (BC). Despite the efficacy of endocrine agents, many patients with luminal BC do not respond to endocrine therapy and many others develop endocrine resistance over time, due to the activation of escape pathways such as the PI3K/AKT/mTOR signaling. Several clinical trials have demonstrated the efficacy of mTOR and PI3K inhibitors in overcoming endocrine resistance in hormone receptor-positive human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…PI3K/AKT favors cell proliferation through direct regulation of cell cycle proteins, the cyclins. [23,40]. Our current research, also indicated that after 48h treating by CPT together with the specific PI3K inhibitor-LY294002, the expression levels of cyclin A, cyclin B, cyclin D and CDK2 were further decreased in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 68%
“…PI3K/AKT favors cell proliferation through direct regulation of cell cycle proteins, the cyclins. [23,40]. Our current research, also indicated that after 48h treating by CPT together with the specific PI3K inhibitor-LY294002, the expression levels of cyclin A, cyclin B, cyclin D and CDK2 were further decreased in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with these studies, 48 h treatment with CPT showed an inhibitory effect on the expression of both PI3K and p-AKT. PI3K/ AKT favors cell proliferation through direct regulation of cell cycle protein, the cyclins [25,41]. Our current results, the expression of cyclin A, cyclin B, cyclin D and CDK2 further decreased with the specific PI3K on PI3K expression by using immunofluorescence assay.…”
Section: Discussionsupporting
confidence: 59%
“…Perhaps, the biggest transformation in breast cancer patient management since these trials were performed, however, is the multiplicity of new systemic therapies currently available for patients with recurrent breast cancer, especially for ER-positive and HER2-positive cancers. [33][34][35][36][37][38] Thus, when these old Italian trials were ongoing, tamoxifen was the only form of systemic endocrine therapy available. In the meantime, additional forms of endocrine therapy such as the aromatase inhibitors and the selective estrogen receptor downregulator (SERD), fulvestrant have become available.…”
Section: Traditional Protein Biomarkersmentioning
confidence: 99%